Methylenetetrahydrofolate reductase homozygous mutation in a young boy with cerebellar infarction - Alberto Spalice; Francesca Del Balzo; Francesco Massimo Perla; Enrico Properzi; Carla Carducci; Italo Antonozzi; Paola Iannetti (MDPI AG, 2009)
Posterior circulation vascular occlusive disease in children is a rare and uncommonly reported event. Among the numerous risk factors, the methylenetetrahydrofolate reductase (MTHFR) mutation is considered to be a common genetic cause of thrombosis in adults and children. Recently, a link between the MTHFR mutation and cerebrovascular disorders was reported in children. Diffusion tensor imaging (DTI) is a great improvement on magnetic resonance imaging (MRI), making the in vivo anatomical and pathological study of the brain and its fibers possible. In our patient cerebellar infarction was associated with MTHFR mutation and, in a standard neurological examination, DTI revealed normal white matter tracts.